Efficiency of health in the regions of Peru, 2012-2019 - Moreno Jaime, Fabiola (2022)
During the COVID-19 pandemic, Peru positioned itself as the country with the highest mortality rate per 100,000 inhabitants worldwide. This fact made evident, among other factors, the limitations of the health system, especially in the interior of the country. Therefore, under a production function approach, the efficiency rates were estimated for the 24 regions in a pre-pandemic period, to show existing gaps, both in inputs and in health outcomes. Methodology: application of a parametric method of stochastic frontiers, model Battese and Coelli (1988), considering health care as the outcome variable and capital, labor and public spending as inputs. In addition, a reference country (the United States) is incorporated to measure the efficiency gaps. Results: the efficiency index of the United States is equal to 1, proving to be a frontier; the average efficiency of the regions of Peru is 0.70; the most efficient region is Ayacucho (0.95) it achieves greater production with less inputs while the least efficient is Moquegua (0.23).